The Relationship of Tax Revenues to Indicators of Economic Development in Iraq (International Journal of Psychosocial Rehabilitation, 2020)
The financing system for developing the economy is based on various sources and resources, the most important of which are tax revenues. Therefore, the relationship between these revenues and development indicators is an important and influential relationship in the economic reality. The imbalance or relative weakness of this relationship will be reflected in the developmental economic reality. Therefore, this relationship must be studied by diagnosing it with the indicators of the development process in Iraq. By analyzing its most prominent indicators of output and finance and the rate of inflation and investment, through the hypothesis that the relationship between tax revenues and economic development indicators is positive. The research found the relative weakness of the contribution of tax revenues in its relationship with indicators of economic development in Iraq.